2016
DOI: 10.4037/ccn2016861
|View full text |Cite
|
Sign up to set email alerts
|

Norwood Procedure for Palliation of Hypoplastic Left Heart Syndrome: Right Ventricle to Pulmonary Artery Conduit vs Modified Blalock-Taussig Shunt

Abstract: Patients with hypoplastic left heart syndrome undergo a series of operations to separate the pulmonary and systemic circulations. The first of at least 3 operations occurs in the newborn period, with a stage I palliation. The goal of stage I palliation is to provide pulmonary blood flow and create an unobstructed systemic outflow tract. Advances in surgical techniques and intraoperative and postoperative care have helped decrease morbidity and mortality for patients with hypoplastic left heart syndrome who hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Infants with cCHD require frequent monitoring of physiological parameters including evaluation of heart rate and rhythm, blood pressure, central filling pressures, perfusion, volume status, urine output, and temperature regulation. 32 Many are physiologically fragile, with minimal reserve to adapt to stressors in the environment. Routine nursing is a source of stress, impacting both sleep and pain.…”
Section: Unique Considerations For the Infant With Cchdmentioning
confidence: 99%
“…Infants with cCHD require frequent monitoring of physiological parameters including evaluation of heart rate and rhythm, blood pressure, central filling pressures, perfusion, volume status, urine output, and temperature regulation. 32 Many are physiologically fragile, with minimal reserve to adapt to stressors in the environment. Routine nursing is a source of stress, impacting both sleep and pain.…”
Section: Unique Considerations For the Infant With Cchdmentioning
confidence: 99%
“…The RCDP methodology (Figure 2) originally developed by Hunt et al 8 has been well received owing to the ease of debriefing and the time-to-task type of training. The RCDP simulation curriculum was based on the model of expert performance and deliberate practice described by Ericsson et al 20 Ericsson 21 identified 3 Cautious volume administration to augment systemic cardiac output PRBCs may be used if there are continued signs of inadequate oxygen delivery in the face of anemia [12][13][14][15] Vasoactive agent adjustment or administration Cautious adjustment of vasoactive agents to augment systemic cardiac output through an increase in systemic BP to maintain appropriate coronary perfusion pressure while avoiding excessive vasoconstriction, which would increase SVR [12][13][14][15][16] Ventilator It is imperative to ensure adequate ventilation, as bicarbonate will be metabolized to CO 2 , which must be able to be cleared through exhalation. When chosen, this maneuver is meant only as a quick, temporary improvement in BP while the other maneuvers are being implemented, as it will not correct the underlying etiology resulting in the acidosis and has side effects that must be considered.…”
Section: Rapid Cycle Deliberate Practicementioning
confidence: 99%
“…When chosen, this maneuver is meant only as a quick, temporary improvement in BP while the other maneuvers are being implemented, as it will not correct the underlying etiology resulting in the acidosis and has side effects that must be considered. 12,17,18 Calcium administration Neonates do not have adequate calcium reserve in the endoplasmic reticulum as adults do, such that hypocalcemia (low ionized calcium level) with hypotension in a neonate (as in this case) can be treated with calcium repletion to augment cardiac output (calcium could act as an inotrope). Calcium may also be important to avoid rhythm disturbance.…”
Section: Rapid Cycle Deliberate Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Surgically, we can bypass the right or left ventricle but with the permission of the almighty respiratory pump [4]. As a reminder, endothelium is the precursor of the cardiovascular system, depends on shear stress of bloodstream to maintain its functions like vascular tone, coagulation, angiogenesis, apoptosis, diabetes, atherosclerosis, immune system, inflammatory response, nitric monoxide synthesis, etc.…”
Section: Introductionmentioning
confidence: 99%